2001
DOI: 10.1300/j051v10n02_06
|View full text |Cite
|
Sign up to set email alerts
|

Student Acceptance of a Multicultural Education

Abstract: While the virtues of a multicultural education are debated in the general US populace, most social work educators and organizations have embraced such an approach. Subsequently, social work journals have offered numerous essays on multicultural teaching techniques. Yet, these same journals have rarely explored the multicultural attitudes of social work students. To fill this gap, this paper empirically explores the ways in which BSW students accept or reject some multicultural goals. To do so, close-ended surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…They attributed school dropout to individual conflicts between students based on ethnic history or religion, culturally-inspired gender roles, having a "culturally-colored perspective" about education and earning a degree, and parents' lower educational aspirations due to cultural differences. On the one hand, the latter is in line with studies showing that the educational aspirations of parents, social workers, teachers, peers, and other close relatives affect the students' attitudes toward education (Cheng & Starks, 2002;Swank et al, 2001). On the other hand, this finding is contrary to previous research, showing that parental involvement and the educational aspirations of the parents are more associated with their educational level (cf.…”
Section: Discussionsupporting
confidence: 80%
“…They attributed school dropout to individual conflicts between students based on ethnic history or religion, culturally-inspired gender roles, having a "culturally-colored perspective" about education and earning a degree, and parents' lower educational aspirations due to cultural differences. On the one hand, the latter is in line with studies showing that the educational aspirations of parents, social workers, teachers, peers, and other close relatives affect the students' attitudes toward education (Cheng & Starks, 2002;Swank et al, 2001). On the other hand, this finding is contrary to previous research, showing that parental involvement and the educational aspirations of the parents are more associated with their educational level (cf.…”
Section: Discussionsupporting
confidence: 80%
“…Other studies reported both positive and negative outcomes, where the latter was often fueled by a sense of White guilt (Boatright-Horowitz et al, 2012;Kernahan and Davis, 2007). Students' beliefs toward White guilt, White privilege, and in American meritocracy (Swank et al, 2001;Asada et al, 2003;Munroe and Pearson, 2006) have also been linked to their acceptance of multicultural learning environments. These constructs, however, do not measure students' degree and expressions of resistance when confronted with dissonance-provoking stimuli in multicultural spaces.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…They found that students' awareness of racism increased between the beginning and end of the class and that students agreed that "action is needed and that they should take responsibility" (Kernahan and Davis, 2007, p. 51). In the context of these findings, and similarly designed studies in the multicultural higher education literature (Boatright-Horowitz et al, 2012;Case, 2007;Munroe and Pearson, 2006;Swank et al, 2001), the PIE-S is a complementary measure that can demonstrate the different ways that individuals take action to alleviate discomfort because of their newfound awareness or guilt. As aforementioned, individuals are motivated to protect themselves from the discomfort that new information causes (Harmon-Jones and Mills, 2019), particularly in relation to privileged social identities (Watt, 2015).…”
Section: Comparing the Four And Eight Pie Factorsmentioning
confidence: 99%
“…They were also demonstrably more likely to email back White help seekers, and less likely to email back minorities. This difference in responsiveness by male and female providers toward help seekers of different races is unfortunate, but to some degree expected and is corroborated by the broader literature on gender differences in racial attitudes and biased behaviors (Alvarez & Domenech Rodríguez, 2020;APA, 2018;David, 2014;Johnson & Marini, 1998;Nosek et al, 2007;Qualls et al, 1992;Radke et al, 2016;Roberts et al, 2019;Sidanius & Pratto, 1999;Smith et al, 2013), as well as the more limited research on mental health care providers (Maxie et al, 2006;Swank et al, 2001). Despite the importance of these findings and the many strengths of this study (e.g., large sample size, randomization of providers, multiple racial groups examined, diagnostic and socioeconomic issues explored, and the first to study email responsiveness), a number of limitations deserve mentioning.…”
Section: Probabilitymentioning
confidence: 92%